2021
DOI: 10.24996/ijs.2021.62.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pentosidine with Kidney Diseases in Iraqi Patients with Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a principle cause of microangiopathy and the main reason for kidney disease at the end stage in patients with type 2 diabetes mellitus (T2DM). This work aimed to study the relation of pentosidine with kidney injury in the case of diabetic nephropathy. This study included 75 patients suffering from T2DM and 75 apparently healthy subjects. The patients group was divided into three groups ((normoalbumin, microalbuminuria, and macroalbuminuria; 25 patients for each) on the basis of alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Later research showed that the adenine receptor is connected to the inhibitory G protein (Gi), which, when activated, suppresses the activity of adenylate cyclase and results in a decrease in the generation of intracellular cAMP. The proximal tubule, collecting duct system, and thick ascending limb are the primary parts of the nephron that participate in the control of numerous kidney water and electrolyte homeostatic activities [19]. Adenine receptors interpose in the suppression of V2 receptor analogs and are expressed in glomerular capillaries, cerebral arterioles, and the collecting duct system.…”
Section: Renal Functionmentioning
confidence: 99%
“…Later research showed that the adenine receptor is connected to the inhibitory G protein (Gi), which, when activated, suppresses the activity of adenylate cyclase and results in a decrease in the generation of intracellular cAMP. The proximal tubule, collecting duct system, and thick ascending limb are the primary parts of the nephron that participate in the control of numerous kidney water and electrolyte homeostatic activities [19]. Adenine receptors interpose in the suppression of V2 receptor analogs and are expressed in glomerular capillaries, cerebral arterioles, and the collecting duct system.…”
Section: Renal Functionmentioning
confidence: 99%
“…Recently, several studies about plant extracts were conducted that included their properties in nano size, antioxidant [1][2][3][4] , their phenolic content , and their cytotoxicity due their bio-activities and safety [5][6][7] , in addition to other studies that concerned with diabetes complications [8][9][10][11] . Marjoram is an aromatic herbaceous plant and it is from the famous mint group and contains many vitamins and minerals, as well as volatile oils, flavonoids, hydroquinone glycosides, sugars, and triterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed great interest in diabetes and its complications. More recently, the association between diabetes and periodontitis has been investigated [1][2][3] ,as studies have shown that patients with high blood sugar suffer from persistent inflammation, and many studies were conducted previously, including diabetic kidney disorders .A phenomenon known as diabetic kidney disease (DKD) is characterized by alterations in the glomerular filtration rate, leakage of protein (particularly albumin), metabolites, and ions into the urine (GFR) [4][5][6][7] , diabetic neuropathies previous studies found that about half of diabetic patients have neuropathy, which consists of weakness in the peripheral nerves and may occur in various ways, including sensory, focal/multifocal, and autonomic neuropathy [8][9][10][11] , and the relationship between diabetes and osteoporosis increases blood sugar and decreases insulin secretion leading to an increase in susceptibility to osteoporosis [12][13][14] , in addition to a number of other studies in the field of diabetes treatments in which blood sugar was naturally controlled in patients with type 2 diabetes 15,16. Diabetic kidney disease is an illness of the glomerulus that interferes with the glomerular filtration barrier (GFB). It works in tandem to enable water and solutes to be selectively purified, while limiting the movement of large macromolecules such as albumin 17 .…”
Section: Introductionmentioning
confidence: 99%